Evaluating the effectiveness of Red Ginger Aromatherapy Essential Oil (Zingiber Officinale Var Rubrum) in treating Emesis Gravidarum in Pregnant Women - rahayu; Catherine Jusuf, Elizabet; Hetharia, Christine; Saleng, Hasriani (Jurnal Ilmiah Kesehatan, 2025)
Emesis gravidarum is vomiting during pregnancy, mainly caused by increased Human Chorionic Gonadotropin (hCG) in the endocrine system. This paper evaluates the effectiveness of red ginger aromatherapy essential oil (Zingiber Officinale var Rubrum) in treating emesis gravidarum among pregnant Women in the first trimester. The research was quasi-experimental using a one-group Pretest-Posttest design. The sample was 30 respondents using purposive sampling. Pregnant women in the 1st trimester who experienced emesis gravidarum inhaled red ginger essential oil aromatherapy using a diffuser once a day for 7 days. The instrument used was the Pregnancy Unique Questionnaire of Emesis (PUQE) to determine the severity of nausea and vomiting in pregnant women. Data were analyzed using the dependent t-test with α=0.05. The results showed that before giving red ginger essential oil aromatherapy, 30 respondents (100%) had mild nausea and vomiting. After intervention, 28 (80%) respondents had no nausea and vomiting, and 2 (20%) had mild nausea and vomiting. In addition, the average PUQE score in respondents before giving red ginger essential oil aromatherapy was 9.13, while after intervention, the mean PUQE score was 5.80. The dependent t-test obtained p=0.000 (p<α), indicating that red ginger essential oil aromatherapy significantly affected the severity of nausea and vomiting in pregnant women. In conclusion, red ginger essential oil aromatherapy can significantly reduce the severity of nausea and vomiting in pregnant women. Thus, it can be used as a non-pharmacological therapy to treat emesis gravidarum in pregnant women.